#### Answer

$(x-3)^2=x^2-6x+9$

#### Work Step by Step

The second term of the square of a binomial is missing.
$(a-b)^2=a^2-2ab+b^2$
So:
$(x-3)^2=x^2-2(x)(3)+3^2=x^2-6x+9$

Chegg costs money, GradeSaver solutions are free!

Published by
Cengage Learning

ISBN 10:
9781337271172

ISBN 13:
978-1-33727-117-2

$(x-3)^2=x^2-6x+9$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.